MEKANISME KOPING WANITA PREMENOPAUSE - Mariyati; Nurul Fazila2; Inong Sri Rahayu3; Ida Suryawati (Jurnal Assyifa: Jurnal Ilmu Kesehatan Lhokseumawe, 2022)
Women's unpreparedness in dealing with Perimenopause signs and symptoms is one of the factors that can affect coping mechanisms. If a woman is not ready to face premenopause and the psychosocial environment does not provide positive support, then the woman's physical and mental health will be affected. This study aims to describe the coping mechanisms of premenopausal women. This study uses a descriptive research design. The population in this study were premenopausal women aged 45-50 years, totaling 100 people. Sampling using an accidental sampling technique with a target sample of 99.99% of the total population of 94 people. Data collection techniques using a questionnaire sheet. The results of univariate data analysis showed that the majority of respondents had threshold coping mechanisms, namely 60 respondents (63.8%), compared to 19 respondents (20.2%) who had maladaptive coping mechanisms, and only 15 (16.0%) respondents who had have adaptive coping mechanisms. The majority of premenopausal, have threshold coping mechanisms. So it is recommended to be able to improve coping mechanisms by implementing their knowledge related to premenopausal signs in the form of adaptive behavior to all signs and symptoms of premenopausal experienced.